2019
DOI: 10.1038/s41467-019-10458-9
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-associated macrophages exhibit anti-tumoural properties in Sonic Hedgehog medulloblastoma

Abstract: Medulloblastoma, which is the most common malignant paediatric brain tumour, has a 70% survival rate, but standard treatments often lead to devastating life-long side effects and recurrence is fatal. One of the emerging strategies in the search for treatments is to determine the roles of tumour microenvironment cells in the growth and maintenance of tumours. The most attractive target is tumour-associated macrophages (TAMs), which are abundantly present in the Sonic Hedgehog (SHH) subgroup of medulloblastoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 34 publications
11
85
0
Order By: Relevance
“…In contrast to M2-M, NA-microglia trended toward being less abundant in SHH compared to GP3 and GP4 in scRNAseq samples (27-fold)( Figure 5E) and were significantly less abundant in SHH in the larger MAGIC cohort (4-fold, p=9.4x10 -16 )( Figure 5F). These findings are congruent with prior studies that identified a less immune active phenotype in GP3 and GP4 than SHH (Margol et al, 2015;Maximov et al, 2019). (Table S5).…”
Section: Thesupporting
confidence: 92%
“…In contrast to M2-M, NA-microglia trended toward being less abundant in SHH compared to GP3 and GP4 in scRNAseq samples (27-fold)( Figure 5E) and were significantly less abundant in SHH in the larger MAGIC cohort (4-fold, p=9.4x10 -16 )( Figure 5F). These findings are congruent with prior studies that identified a less immune active phenotype in GP3 and GP4 than SHH (Margol et al, 2015;Maximov et al, 2019). (Table S5).…”
Section: Thesupporting
confidence: 92%
“…With the high-speed development of omics, high-throughput tumor databases have been established, including TCGA and CGGA, which provided a solid foundation for analyzing the RNA modification and microenvironments of glioma ( 3 , 44 – 46 ). One of the emerging strategies of management is based on the roles of immune cells in the growth and maintenance of tumors ( 47 ). According to the recent studies, myeloid-derived suppressor cells (MDSC) and tumor-associated macrophages (TAMs) have been identified as promising targets for anti-cancer treatment ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we were able to construct four PPI modules, all of which were related to critical GBM biological processes. Highly relevant nodes in the modules, including STAT3, SLC11A1, and ITGAM, have been reported to promote tumor proliferation, angiogenesis, migration, and invasiveness (73)(74)(75)(76)(77). Among the 64 genes validated, 27 (such as ALOX5, CAST, HS6ST1, ITGAM, PTPN6, SLC11A1, and SLC12A7) have been reported to be involved in the pathogenesis of GBM or critical in predicting OS.…”
Section: Discussionmentioning
confidence: 99%